Cytotoxicity Enhancement Of Low-Level Laser Irradiation On Gold Nanoparticles In Human Breast Cancer Mcf-7 Cell Line - Habita @ Habit, Husna Azdiyah (2020)
Laser light is another option used to provide non-invasive or less invasive cancer therapy. In this study, low-level laser therapy (LLLT) is used as it is less invasive due to lower energy densities than other types of laser with a combination of gold nanoparticles (AuNPs) to enhance the effects of radiation in the MCF-7 breast cancer cell line. In this work, the cells were seeded in 96-well plate and were treated with 50 nm AuNPs before irradiated with a laser for 0.002 W, 0.02 W, 0.06 W, and 0.1 W at various time from 60 s to 900 s. Then, the irradiated cells with AuNPs were incubated for 24 h. After that, the absorbance of irradiated cells was measured by Alamar Blue to determine the cell viability. The result shows without AuNPs in all irradiation conditions, less cell inhibition occurred with viability percentage in range between 50 to 70 % indicating that the cells were less affected by the laser due to multifactor of radio-resistance. However, a clear reduction in cell density exceeding 90 % was observed for cells irradiated with dose of 2.40 J/cm2 in the presence of AuNPs with highest concentration 50 μg/ml when compared to AuNPs alone or laser alone. This clearly indicates that the AuNPs are required for photothermal conversion of the green laser irradiation, which induces cell death. Considering the effects on the MCF-7 cells proliferation and the results of viability cells, AuNPs-assisted laser therapy turned out to have a satisfactory treatment effect as expected.